2016
DOI: 10.1097/scs.0000000000003138
|View full text |Cite
|
Sign up to set email alerts
|

Angular Relationship Between the Foramen Ovale and the Trigeminal Impression

Abstract: The debilitating pain of trigeminal neuralgia (TN) often necessitates neurosurgical intervention via percutaneous transovale cannulation. While most percutaneous treatments of TN are successful, severe adverse events resulting from failure to properly cannulate the foramen ovale (FO) have been reported. With regard to specific targeting of particular trigeminal divisions (i.e. V1, V2, V3, and combinations thereof), operative techniques have been described; however, these descriptions have not included specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…Thus, it is necessary to perform the individualized compression pressure monitoring for PBC procedure. Despite the balloon shape, the cannulation of FO is also important for PBC and the diversity of the FO shape may contribute to the operative difficulties [29]. To facilitate the cannulation, the reconstruction of the FO is useful with CT navigation perioperatively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is necessary to perform the individualized compression pressure monitoring for PBC procedure. Despite the balloon shape, the cannulation of FO is also important for PBC and the diversity of the FO shape may contribute to the operative difficulties [29]. To facilitate the cannulation, the reconstruction of the FO is useful with CT navigation perioperatively.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that PBC is an effective and safe option for the elderly population [ 28 ]. The other advantage of PBC is the considerable high success rate for recurrence TN after PBC or other unsuccessful treatment [ 29 ]. However, we excluded the participants who were treated with previous MVD or destructive trigeminal surgery to avoid the potential bias in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The results also coincide with the anatomical structure of the trigeminal nerve. 8,17 As mentioned above, the cucumber shape was di cult to obtain normally. If a cucumber shape was failed to achieve, the catheter would be pulled backwards and maintain a little tension when the balloon was almost round.…”
Section: Discussionmentioning
confidence: 99%
“…e inclusion criteria were as follows: (1) patients aged >18 years; (2) patients with only primary V1 trigeminal neuralgia, or combined with V2/V3 trigeminal neuralgia; (3) patients with preoperative Numerical Rating Scale (NRS) score of >5; (4) patients with disease course of >1 month; and (5) patients whose pain was not relieved after treatment with carbamazepine, gabapentin, or pregabalin alone or in combination, or the patient could not tolerate the adverse responses. e exclusion criteria were as follows: patients (1) who undergoes routine CT scanning of the paranasal sinus and MRI examinations of trigeminal nerve before the operation suggesting secondary trigeminal neuralgia; (2) with trigeminal neuralgia secondary to herpes zoster; (3) with local infection at the site of puncture; (4) with psychiatric disorders or intellectual disability; (5) with severe liver, kidney, heart, or lung diseases; and (6) with coagulation disorders before operation, or allergic to local anesthetics. All the surgical protocols were approved by the Ethics Committee of the First Hospital of Jiaxing.…”
Section: Subjectsmentioning
confidence: 99%
“…Radiofrequency treatment for trigeminal neuralgia has shown definitive treatment efficacies [3]. However, with conventional radiofrequency therapy of Gasserian ganglion through foramen ovale, the sense and movement in the areas innervated by the ophthalmic nerve, which is the first branch of trigeminal nerve, may not be detected despite perfect puncturing, leading to severe complications, such as blindness induced by corneal ulcer [4].…”
Section: Introductionmentioning
confidence: 99%